Left and Right. Meaning and Correlates in Long Consolidated and New Democracies - Freire, A. (2022)
After the French Revolution, the idea of a left-right (LR) divide gained importance in mass politics, especially in the West. At the systemic level, LR formed a code of communication between politicians, mass media and voters; at the individual level, it has been an instrument to orient voters in how to deal with the political realm. Various studies in several regions of the world have documented the remaining importance of electors’ positions on the LR scale as a defining factor of their voting choices. Additionally, it has been shown that even in «less central» parts of the world (Latin America and East Asia) a large majority of citizens «correctly» recognize and use the LR divide. Finally, it has been shown that around the globe individual LR SP (Self-Placement) is also anchored on values. However, it can be said that in several dimensions of the left-right divide comparisons between long consolidated and new democracies are relatively rare, at least up to a certain date. Bearing upon articles previously published in different academic journals (Party Politics; International Political Science Review; Pôle Sud; Brazilian Political Science Review; Journal of Political Ideologies; Comparative European Politics; Communist and Post-Communist Studies; Journal of Legislative Studies) and a 2020 book chapter, from Rowman & Littlefield, this book uncovers four major topics, organized in Four Parts: I - left and right in long consolidated and new democracies (5 chapters), II- the meaning and social correlates of Left and Right (3); III- Left and Right in Portugal: voters and parties (2); IV - Left and Right among citizens and representatives: the Portuguese case (2). Blurbs (2) for: Freire, Left, and Right. Meaning and Correlates in new and Long Consolidated Democracies, Moldova, Eliva Press, 2022. André Freire has authored an impressive study on Left-Right (L-R) orientations in contemporary democracies. The most intriguing elements of this book are the varied meanings and consequences of L-R orientations across established and new democracies. This is a valuable resource especially for those studying the L-R framework in contemporary party systems. Russell J. Dalton University of California, Irvine Analysing the sources and effects of L-R orientations in mass publics in different parts of the world at different times, this book presents an inspiring collection of articles. Certainly, the sum of these contributions amounts to much more than its parts. Hermann Schmitt Research Fellow, Mannheimer Zentrum für Europäische Sozialforschung Emeritus Professor, Faculty of Humanities, University of Manchester